Effectiveness of literacy and numeracy in commerce subjects among secondary schools in Fiji - Devashna Singh; Satish Prakash Chand; Khemendra Kamal Kumar; Runaaz Ali (Intelektual Pustaka Media Utama, 2023)
This study aimed to evaluate the students’ efficacy in literacy and numeracy skills in commerce subjects in secondary schools in Fiji. Focus group discussions and semi-structured interviews were used to gather relevant data. The findings show that literacy and numeracy skills are essential in commerce subjects, as students require basic literacy and numeracy skills to read, write, comprehend, calculate, and interpret. The findings also showed that parental engagement at an early stage of the child’s life helps improve the child’s literacy and numeracy skills. The results also showed that the “drop everything and read” or DEAR programme and modern technology positively affect students’ literacy and numeracy skills, which helps them do better in commerce classes.